ADDRESSING COMMUNITY BASED PROBLEMS: EXPLORING THE ROLE OF CBO THROUGH PARTICIPATORY APPROACH - Sadya Islam; Antora M. Haque; Mohammad T. H. Shubho; Ishrat Islam; Farzana Khatun; Dipita Hossain (European Scientific Journal, ESJ, 2014)
Urban and rural communities in a country are sometimes confronted with many problems which are well understood by the community residents itself. A Community Based Organization (CBO), in this regard, can play the major role to solve these problems by selfinitiative participatory approach. Community Based Organization (CBO) is such a non-profit institute which operates within a community to provide the local services and is usually run by the local people of that community. Rather depending on local/central government, the community itself can solve certain problems with the assistance of local people and CBOs. In such backdrop, this research was intended to unfold the role of CBO in improving the urban community through Participatory Reflection and Action (PRA) method. The study is based on an urban CBO of Lalbag Thana in South Dhaka, Bangladesh. This research was intended to identify the major problems, their causes and effects on the study area and possible solutions of those problems through active participation of both CBO and its people. Several PRA tools were employed to obtain the objectives. Sewerage and drainage problem, poor water quality and water supply, narrow and poor condition of access roads etc. were the major problems. Effective solutions came forth from the locality for solving those problems such as: provision of water extraction pump and reservoir, drain cover and street dustbins and enforcement of building bye-laws etc. Whilst having the potential, the CBO was found inadequate to implement the solutions due to lack of resource mobilization. However, success of this research is a clear indication that community improvement is possible through mobilization of CBO and ensuring public participation.